THE DEVELOPMENT OF CARDIOLOGY AS A SCIENCE - Ismatova Jamila (Journals Park Publishing, 2022)
Cardiology (from cardio... and ...logy), a branch of medicine that studies the structure, function, diseases of the heart and blood vessels, their causes, mechanisms of development, clinical manifestations, diagnostics, as well as developing methods of treatment (including surgical), prevention, issues of medical rehabilitation of patients with lesions of the cardiovascular system. The article provides an overview of the wound, development of Cardiology in medicine and its centuries—long development.
Keywords: Cardiology; including surgical; doctors